Postoperative Delirium Developed After Open Prostatectomy Under Spinal Anaesthesia: A Case Report - Aydoğmuş, Meltem; Tükenmez, Barış (Fırat University, 2012)
Post-operative delirium is seen after long-duration surgery such as vascular and orthopedic surgical procedures with higher incidence. Delirium is associated with higher post-operative mortality, morbidity and delayed functional recovery. Advanced age, post-operative pain and sleep problem were important factors for delirium. Therefore post-operative analgesia and good sleep can help to prevent post-operative delirium. The use of intraoperative regional anesthesia does not certain to decrease the incidence of post-operative deliryum when compared with general anesthesia. Neuroleptics such as haloperidol, droperidol and benzodiazepines are used in order to control symptoms like restlessness, agitation and altered perceptions. We aimed to discuss in this case post-operative delirium that developed after open prostatectomy and cystolithotomy under spinal anaesthesia.

Post-operatif deliryum, vasküler ve ortopedik cerrahi gibi uzun süren prosedürler sonrasında yüksek insidansta görülür. Yüksek mortalite ve morbidite ile birlikte fonksiyonel iyileşmede gecikmeye neden olur. Deliryum için yaş, post-operatif ağrı ve uyku problemleri en önemli risk faktörleridir. Bu nedenli post-operatif analjezinin iyi düzenlenmesi ve uyku bozukluğunu düzeltilmesi deliryumun önlenmesine yardımcıdır. Genel anesteziye karşın intra-operatif rejyonel anestezinin post-operatif deliryum yapma olasılığının daha düşük olduğu önerilse de bu kesin değildir. Huzursuzluk, algılama bozukluğu ve ajitasyon benzeri semptomların kontrolünde haloperidol, droperidol gibi nöroleptikler ve benzodiazepinler kulanılmaktadır. Biz bu olguda spinal anestezi altında yapılan açık prostatektomi ve sistolitotomi sonrası gelişen post-operatif deliryumu tartışmayı amaçladık.
Spinal Anestezi Altında Yapılan Açık Prostatektomi Sonrası Gelişen Postoperatif Deliryum: Olgu Sunumu